2017
DOI: 10.3389/fpubh.2017.00179
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence of Colorectal Cancer in Adolescents and Young Adults Aged 15–39 Years in Western Australia 1982–2007: Examination of Colonoscopy History

Abstract: AimsTo examine trends in colorectal cancer (CRC) incidence and colonoscopy history in adolescents and young adults (AYAs) aged 15–39 years in Western Australia (WA) from 1982 to 2007.DesignDescriptive cohort study using population-based linked hospital and cancer registry data.MethodFive-year age-standardized and age-specific incidence rates of CRC were calculated for all AYAs and by sex. Temporal trends in CRC incidence were investigated using Joinpoint regression analysis. The annual percentage change (APC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 39 publications
4
60
0
1
Order By: Relevance
“…Our findings are consistent with previous work in Australia (8)(9)(10) but provide a greater level of detail over a longer time period, with information on specific trends in colon and rectal cancer, with the inclusion of over 375,000 cases in our analysis. A previous study analyzed incidence rates from 1990, 1995, 2000, 2005, and 2010 and found that colorectal cancer incidence was increasing for those under 40 years of age but was stable or declining in those ages 40 to 59 years (9).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with previous work in Australia (8)(9)(10) but provide a greater level of detail over a longer time period, with information on specific trends in colon and rectal cancer, with the inclusion of over 375,000 cases in our analysis. A previous study analyzed incidence rates from 1990, 1995, 2000, 2005, and 2010 and found that colorectal cancer incidence was increasing for those under 40 years of age but was stable or declining in those ages 40 to 59 years (9).…”
Section: Discussionsupporting
confidence: 91%
“…A study from the United States showed that the risk of colon and rectal cancer was two‐ (incidence rate ratio (IRR) = 2.40, 95% confidence interval (CI) 1.11 to 5.19) and four times higher (IRR = 4.32, 95% CI 2.19 to 8.51), respectively for those born circa 1990, compared to adults born circa 1950. Similarly, in Western Australia, between 1982 and 2007, a 3.0% annual increase in CRC incidence was observed among adolescents and young adults (15–39 years) . As screening is usually recommended for adults aged 50 to 75, changes in incidence in this group is most likely not impacted by screening.…”
Section: Discussionmentioning
confidence: 99%
“…As screening is usually recommended for adults aged 50 to 75, changes in incidence in this group is most likely not impacted by screening. Possible explanations are changes in the prevalence of risk factors such as increasing body weight and lower physical activity …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations